Natural history of frozen shoulder: fact or fiction? A systematic review. Issue 1 (March 2017) - Wong, C.K.; Levine, W.N.; Deo, K.; Kesting, R.S.; Mercer, E.A.; Schram, G.A.; Strang, B.L.
Abstract: Background: In 1940s, it was proposed that frozen shoulder progresses through a self-limiting natural history of painful, stiff and recovery phases, leading to full recovery without treatment. However, clinical evidence of persistent limitations lasting for years contradicts this assumption. Objectives: To assess evidence for the natural history theory of frozen shoulder by examining: (1) progression through recovery phases, and (2) full resolution without treatment. Data sources: MEDLINE, PubMed, EBSCO CINAHL and PEDro database searches augmented by hand searching. Study selection: Cohort or randomised controlled trials with no-treatment comparison groups including adults with frozen shoulder who received no treatment and reporting range of motion, pain or function for ≥6 months. Data extraction: Reviewers assessed study eligibility and quality, and extracted data before reaching consensus. Limited early range-of-motion improvements and greater late improvements defined progression through recovery phases. Restoration of normal range of motion and previous function defined full resolution. Results: Of 508 citations, 13 articles were reviewed and seven were included in this review. Low-quality evidence suggested that no treatment yielded some, but not complete, improvement in range of motion after 1 to 4 years of follow-up. No evidence supported the theory of progression through recovery phases to full resolution without treatment. On the contrary, moderate-quality evidence from three randomised controlled trials with longitudinal data demonstrated that most improvement occurred early, not late. Limitations: Low-quality evidence revealed the weakness of longstanding assumptions about frozen shoulder. Conclusion: Contradictory evidence and a lack of supporting evidence shows that the theory of recovery phases leading to complete resolution without treatment for frozen shoulder is unfounded.